Manufacturing method of artificial light-transmitting stone embossment

Through the combination of bio-based polyurethane resin and nanofiller and the dual curing process, the problems of high density, brittleness and low transmittance of translucent stone reliefs were solved, and a relief material with high transmittance, low density and good weather resistance was achieved, which is suitable for high-end decoration and outdoor applications.

CN120663681APending Publication Date: 2025-09-19SHENZHEN SHANGCHUAN CONSTR GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510805632.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Existing translucent stone relief materials have problems such as high density, high brittleness, low transmittance, difficulty in processing, and poor weather resistance, making it difficult to meet the needs of high-end decoration and industrial production.

Method used

By mixing bio-based polyurethane resin with aliphatic isocyanate, combining the dispersion technology of nano-silica and glass beads, and through UV-heat dual curing and air pressure embossing process, a translucent stone relief with high transmittance, low density and good weather resistance is prepared.

Benefits of technology

It has achieved a transmittance of ≥70%, a density of 1.2-1.5g/cm3, a Shore hardness of 65A, good yellowing resistance, and is suitable for high-end decoration and outdoor applications. It reduces dependence on fossil resources and VOC emissions and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120663681A_ABST
    Figure CN120663681A_ABST
Patent Text Reader

Abstract

The invention discloses a manufacturing method of an artificial light-transmitting stone embossment, which is realized by the following steps of: mixing bio-based polyurethane resin with aliphatic isocyanate, adding fillers such as polyacrylate, organic silicon, nano silicon dioxide, glass beads and the like, then dispersing, carrying out vacuum defoaming to obtain slurry, and drying to obtain the artificial light-transmitting stone embossment. A layered pouring process is combined with an air pressure impressing technology for forming, the period is shortened through UV-thermal dual curing, and the embossment is manufactured. The bottleneck of a traditional process is broken through, epoxy resin is replaced with bio-based resin, the environment-friendly requirement is met, a diffuse reflection system is formed by nano-silica and glass beads, the light transmittance is larger than or equal to 70%, the surface is glossy, soft and free of glare, the aliphatic isocyanate endows the anti-yellowing characteristic, and compared with a traditional unsaturated polyester and epoxy resin method, the anti-yellowing performance is good. The light transmittance, the weather resistance, the mechanical property and the environmental protection property are remarkably improved, and the light-transmitting and weather-resistant composite material is suitable for high-end building decoration, art relief and other scenes and has the industrial mass production and personalized customization capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite materials, and in particular relates to a method for manufacturing an artificial light-transmitting stone relief. Background Art

[0002] In the field of decorative art and building materials, translucent stone reliefs are highly favored for their unique light and shadow effects, but the development of their preparation technology has been full of breakthroughs and iterations of technical bottlenecks. Early technical systems relied entirely on natural translucent stones, such as mica, jade and other rare minerals, to achieve basic light transmission functions through high-precision ultra-thin cutting processes. However, these natural materials have structural defects: their average density reaches 2.8-3.2g / cm 3 The brittleness index is as high as 6.5-7.0, resulting in a cracking rate exceeding 40% when processing relief shapes with a depth exceeding 5mm. In terms of optical performance, the light transmittance of natural stone is generally less than 50%. Under a 6000K color temperature light source, the diffuse reflectance coefficient of light is only 0.35-0.42, resulting in glare problems with brightness differences exceeding 30% in the illuminated area, seriously affecting visual comfort.

[0003] Entering the era of composite materials, the first technological breakthrough occurred in the resin-based material stage. Using unsaturated polyester resin as the matrix, filled with aluminum hydroxide powder with an average particle size of 5-10μm, and vacuum casting to produce a light-transmitting plate, the density was reduced to 1.8-2.0g / cm 3 , only about 60% of natural stone, successfully addressing the weight issue. However, the process has significant drawbacks. The room-temperature curing cycle is as long as 24-48 hours. A production line with an annual output of 50,000 square meters would require 300 sets of molds to meet this turnover, increasing equipment investment by over 30%. More critically, polyester resin lacks weather resistance. Under ultraviolet radiation, the yellowing index increases by 8-10 units annually. After three years, the light transmittance of the translucent panels drops below 45%, seriously affecting the decorative effect.

[0004] Technological improvements quickly shifted to an acrylic-modified system. By introducing methyl methacrylate monomers for graft copolymerization and combining them with 365nm UV curing technology, the molding cycle was shortened to 30-60 minutes, increasing production efficiency by more than 20 times. Optical properties were also optimized, with transmittance reaching 60%-65%, and average transmittance in the visible light range of 400-700nm increasing by 15%. However, the material's mechanical properties showed new shortcomings: its flexural strength was only 45-50MPa, lower than the 70MPa of natural stone.

[0005] The traditional preparation process also faces bottlenecks. The segmented curing casting process results in 0.5%-1% bubbles remaining inside the material, which easily forms crack sources in stress concentration areas. The efficiency of manual demoulding is low, and the average processing capacity per person in a single shift is only 20-30 pieces. The mold loss rate is as high as 15%. Although the emerging air pressure imprinting technology can achieve millimeter-level texture replication, it requires the mold surface roughness to be below Ra0.1, which increases the processing cost by 40%. When replicating micro-nano structures below 50μm, the texture distortion rate exceeds 25%, which cannot meet the preparation needs of high-precision artistic reliefs. In response to the above-mentioned multiple technical barriers spanning material performance, processing technology, and cost control, this patent proposes a systematic solution that integrates material modification and process innovation, aiming to break through the bottleneck of traditional technology and achieve high performance and industrialized production of translucent stone reliefs. Summary of the Invention

[0006] To solve the problems of poor light transmittance, high natural density, long curing cycle and poor yellowing resistance.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A method for producing an artificial light-transmitting stone relief comprises the following steps:

[0009] S1: Bio-based polyurethane resin and aliphatic isocyanate were mixed in a ratio of 4:1, followed by addition of polyacrylate and silicone in a low-speed mixer at 200 rpm for 3 minutes;

[0010] S2: The mixture in S1 was added with nano-silica and glass beads in batches, and the mixture was dispersed in a disperser at 500 rpm for 5 minutes until no lumps were formed. The mixture was then vacuum degassed for 5 minutes, and finally 0.1% of a transparent organic pigment azo dye was added and stirred to prepare a slurry.

[0011] S3: Pour 0.5mm thick slurry on the bottom of the mold, then let it stand for 5 minutes and irradiate it with UV lamp for 10 minutes to cure it. Place the slurry in the relief area of ​​the mold upside down, use 0.3-0.5MPa air pressure imprinting technology to embed the slurry into the mold texture and let it stand for 15 minutes until it is semi-cured. Finally, pour 1mm thick slurry on the relief to wrap the relief structure, and then vacuum degas.

[0012] S4: Place the whole in a UV curing box and irradiate for 20 minutes to cure the surface layer, then transfer to a 60°C oven for 1 hour, then cool to room temperature and remove the mold;

[0013] S5: Polish the relief with 800# and 2000# sandpaper respectively.

[0014] Preferably, the use of bio-based polyurethane and nano-silica in S1 instead of traditional epoxy resin meets environmental protection requirements.

[0015] Preferably, the nano-silica and glass beads described in S1 form a diffuse reflection system, which produces a soft halo effect when light passes through, avoiding the glare of traditional processes.

[0016] Preferably, the raw materials used in S1 replace natural stone, which reduces the cost by 30-50%, and can be customized into different shapes and patterns according to needs.

[0017] Preferably, the 0.1% azo dye used in S2 can achieve a bright and light-transmitting color, so that the light transmittance is ≥70%.

[0018] Preferably, the process described in S3 adopts layered casting and UV-heat dual curing, which shortens the curing cycle of the relief by 50%.

[0019] Preferably, the vacuum degassing in S3 can make the overall density of the relief uniform.

[0020] Preferably, the relief in S4 has a Shore hardness of 60-70A and a bending strength ≥30MPa, which is better than traditional resin relief and can withstand daily collisions.

[0021] Preferably, the aliphatic isocyanate used in the relief in S4 has yellowing resistance and does not change color after 5 years of outdoor use, which is better than aromatic polyurethane.

[0022] Preferably, the density of the relief in S4 is 1.2-1.5 g / cm 3 It is only half the size of natural stone, making it easy to install, transport, and create large-scale wall reliefs.

[0023] Effects and advantages of the method for making an artificial light-transmitting stone relief of the present invention:

[0024] 1. This patent uses bio-based polyurethane resin to replace traditional petroleum-based epoxy resin, reducing dependence on fossil resources from the source. Renewable materials account for more than 40%, VOC emissions are reduced by 60%, and the health risks of residual benzene solvents in traditional resin reliefs are solved.

[0025] 2. The aliphatic isocyanate used in this patent does not contain a benzene ring in its molecular structure. After UV aging test, the color difference ΔE≤1.0, which is significantly better than the ΔE≥4.5 of aromatic polyurethane. It can be used outdoors for 5 years without discoloration, meeting the long-term aesthetic requirements of high-end buildings.

[0026] 3. This patent uses nano-silica and glass microbeads to form nano-micron graded fillers, which are evenly distributed in the slurry after dispersion. Multiple scattering occurs when light passes through, making the transmittance ≥70%. At the same time, the surface gloss is controlled at 30-40GU, ​​avoiding the glare of traditional processes and forming a museum-level soft halo effect.

[0027] 4. This patent, with the addition of 0.1% low-content azo dye, achieves a 40% increase in color saturation without affecting transmittance through molecular-level dispersion technology. It can customize pure color transmittance effects such as red, blue, and green, breaking through the bottleneck of traditional translucent stones with turbid colors and the inability to achieve both transmittance and chroma.

[0028] 5. This patent uses UV pre-curing to quickly form a surface cross-linking layer 10 minutes earlier, fix the details of the embossed texture, and avoid pattern blurring caused by slurry flow. Thermal curing can promote deep cross-linking of internal molecules to form an interpenetrating network structure, making the Shore hardness reach 65A and the bending strength 35MPa. It can withstand a 50cm high free drop test without cracks, meeting the needs of high-frequency collision scenarios in commercial spaces. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The present invention provides a production flow chart of an artificial light-transmitting stone relief. DETAILED DESCRIPTION

[0030] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.

[0031] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus. In the absence of further restrictions, the elements defined by the sentence "include..." do not exclude the presence of other identical elements in the process, method, article or apparatus that includes the elements.

[0032] refer to Figure 1 , Example 1 introduces in detail a method for making an artificial translucent stone relief.

[0033] Example 1

[0034] This embodiment provides a method for producing an artificial light-transmitting stone relief, which is suitable for personalized customization and mass production. The following implementation contents are provided:

[0035] Purpose of the experiment:

[0036] An artificial light-transmitting stone relief is prepared.

[0037] Experimental materials:

[0038] Bio-based polyurethane resin, nano-silica powder, transparent glass microspheres, aliphatic isocyanate, polyacrylate, silicone, 0.1% azo dye

[0039] Experimental steps:

[0040] S1: Bio-based polyurethane resin and aliphatic isocyanate were mixed in a ratio of 4:1, followed by addition of polyacrylate and silicone in a low-speed mixer at 200 rpm for 3 minutes;

[0041] S2: The mixture in S1 was added with nano-silica and glass beads in batches, and the mixture was dispersed in a dispersant at 500 rpm for 5 minutes until no lumps were formed. The mixture was then vacuum degassed for 5 minutes, and finally 0.1% of a transparent organic pigment azo dye was added and stirred to prepare a slurry.

[0042] S3: Pour 0.5mm thick slurry on the bottom of the mold, then let it stand for 5 minutes and irradiate it with UV light for 10 minutes to cure it. Place the slurry in the relief area of ​​the mold upside down, use air pressure imprinting technology to embed the slurry into the mold texture, and let it stand for 15 minutes until it is semi-cured. Finally, pour 1mm thick slurry on the relief to wrap the relief structure, and then vacuum degas.

[0043] S4: Place the whole in a UV curing box and irradiate for 20 minutes to cure the surface layer, then transfer to a 60°C oven for 1 hour, then cool to room temperature and remove the split mold;

[0044] S5: Polish the relief with 800# and 2000# sandpaper respectively.

[0045] Experimental results: See Table 1 for details.

[0046] Table 1: Test results of Example 1

[0047] Light transmittance density Shore hardness UV aging color difference Example 1 75% <![CDATA[1.2g / cm 3 ]]> 65A ΔE=0.8

[0048] The light transmittance of Example 1 reaches 75% and the density reaches 1.2g / cm 3The measured data of Shore hardness 65A and UV aging color difference ΔE=0.8 directly prove the breakthrough advantages of this method in mechanical properties and weather resistance. The Shore hardness is achieved through the synergistic effect of dual curing process and nanofiller, and the UV aging color difference depends on the molecular design of aliphatic isocyanate and the UV shielding effect of nanoparticles.

[0049] Comparative Example 2

[0050] This embodiment provides a method for preparing a traditional artificial light-transmitting stone relief, which is suitable for decoration. The following implementation contents are provided:

[0051] Purpose of the experiment:

[0052] Preparation of traditional artificial translucent stone relief

[0053] Experimental materials:

[0054] 70 parts of unsaturated polyester resin, 1 part of methyl ethyl ketone peroxide, 30 parts of aluminum hydroxide powder, 10 parts of styrene, and 5 parts of acrylate.

[0055] Experimental steps:

[0056] S1: Mix unsaturated polyester resin and styrene in a ratio of 7:3, add silicone defoamer, and stir at a low speed of 100-200 rpm for 5 minutes;

[0057] S2: Add aluminum hydroxide powder in batches, increase the speed to 300-400 rpm, disperse for 10-15 minutes until there is no obvious agglomeration, add 0.5-1% traditional azo dye, and continue stirring for 5 minutes;

[0058] S3: Apply release agent to the mold surface and pour 5-10mm thick slurry at one time. Then let it stand at room temperature for 2 hours to pre-cure, and then transfer it to a 60℃ oven for 8-12 hours without UV auxiliary curing.

[0059] S4: After curing, the mold is manually disassembled and the surface is polished using 600# and 1000# sandpaper, which takes 2-3 hours per piece.

[0060] Experimental results: See Table 2 for details.

[0061] Table 2: Test results of Comparative Example 1

[0062] Light transmittance density Shore hardness UV aging color difference Comparative Example 1 50% <![CDATA[1.5g / cm 3 ]]> 60A ΔE=5

[0063] Traditional methods for producing artificial translucent stone reliefs are limited by petroleum-based materials, a single curing process, and conventional fillers. This results in significant shortcomings in environmental friendliness, light transmittance, weather resistance, and production efficiency, limiting their appeal to low-end markets. A new method, utilizing bio-based resin substitution, nanocomposite fillers, and dual-curing technology, systematically addresses these challenges, advancing this material's application in high-end decoration, outdoor applications, and precision customization. The technical distinction between the two approaches essentially reflects the difference between extensive petroleum-based processing and green, refined manufacturing, reflecting the building materials industry's trend from availability to quality.

[0064] Comparative Example 2

[0065] This embodiment provides a method for preparing an artificial light-transmitting stone relief using epoxy resin, which is suitable for cultural scenes. The following implementation contents are provided:

[0066] Purpose of the experiment:

[0067] Preparation of epoxy resin for artificial translucent stone relief.

[0068] Experimental materials:

[0069] 70 parts of epoxy resin, 15 parts of light-transmitting curing agent, 10 parts of optical grade quartz powder, 5 parts of transparent glass beads, 0.5 parts of silicone, 0.3 parts of UV absorber, and 0.1 parts of azo dye.

[0070] Experimental steps:

[0071] S1: Heat the epoxy resin to 40-50°C, add quartz powder and glass beads, and disperse in a 300-500 rpm mixer for 10 minutes to ensure that the filler is evenly dispersed. After cooling to room temperature, add the curing agent, leveling agent, and UV absorber, and continue stirring for 5 minutes to avoid vigorous stirring to introduce bubbles. Finally, add the transparent pigment and stir at a low speed until the color is uniform.

[0072] S2: Slowly pour the slurry into the pre-treated relief mold, adjust the thickness according to the relief design, put it into a vacuum box, and degas for 5-8 minutes at a pressure of -0.08MPa to eliminate bubbles between the filler and the resin;

[0073] S3: Let it stand at 25℃ for 24 hours, which is suitable for simple molds or small-sized reliefs. Then put it in a 60℃ oven for 2 hours, then increase the temperature to 80℃ and keep it for 1 hour.

[0074] S4: After the curing is complete, disassemble the mold and polish the surface with 1200-2000# sandpaper. If higher light transmittance is required, flame polishing or applying a transparent protective coating can be performed.

[0075] Experimental results: See Table 3 for details.

[0076] Table 3: Comparative Example 2 test results

[0077] Light transmittance density Shore hardness UV aging color difference Comparative Example 2 30% <![CDATA[1.4g / cm 3 ]]> 60HD ΔE≤5

[0078] The traditional unsaturated polyester-based artificial translucent stone in Comparative Example 2 has a lower light transmittance than the acrylate-based material, and its light transmittance index is much lower than that of methyl methacrylate. The system achieves the effect of reducing color difference by adding ultraviolet absorbers, but it still requires maintenance for long-term use. The Shore hardness is poor due to the resin cross-linking degree and filler content.

[0079] Example 1 provides a method for preparing an artificial light-transmitting stone relief based on a bio-based polyurethane resin and aliphatic isocyanate. Through a dual-curing process, graded dispersion of nano-silica and glass microspheres, and layered casting and air pressure embossing technology, a comprehensive performance breakthrough was achieved. Experimental results show that the relief produced by this method has a light transmittance of 75% and a density as low as 1.2g / cm 3 , a Shore hardness of 65A, and a color difference of only ΔE = 0.8 after 500 hours of UV aging. Its core advantages lie in the environmental friendliness of bio-based materials, the optical optimization of nanofillers, and the improved mechanical properties brought by dual curing. It is suitable for high-end decoration, outdoor scenes, and precision customization, demonstrating technological innovation in green and refined manufacturing.

[0080] Comparative Example 1 uses traditional unsaturated polyester resin as the base material, combined with aluminum hydroxide powder and a single thermal curing process. Although it achieves basic light transmittance and molding capabilities, its performance has significant limitations. Experimental data shows that its light transmittance is only 50% and its density is 1.5g / cm 3 , Shore hardness 60A, UV aging color difference ΔE = 5. This method relies on petroleum-based resins and conventional fillers, and has problems such as high VOC emissions, long curing cycles, and poor weather resistance. Furthermore, the pattern reproduction accuracy is low, which only meets the needs of low-end interior decoration. It cannot adapt to the upgrading of environmental protection standards and the long-term aesthetic requirements of the high-end market.

[0081] Comparative Example 2 uses epoxy resin as the base material. By adding optical grade quartz powder, UV absorber and heating curing process, the chemical resistance and hardness are improved to a certain extent. However, the light transmittance is only 30%, which is significantly lower than that of the new method. The density is 1.4g / cm 3 The UV aging color difference ΔE ≤ 5 still requires post-processing and maintenance. The core bottleneck of this method is that the aromatic structure of epoxy resin leads to limited yellowing resistance. Moreover, the filler dispersion process and single curing method make it difficult to achieve a balance between light transmittance and mechanical properties. The application scenarios are limited to low- and mid-end applications with high chemical resistance requirements. It is unable to balance environmental protection, efficiency and overall performance.

[0082] The light transmittance of Example 1 is 75%, far exceeding the 50% of Comparative Example 1 and 30% of Comparative Example 2. The nano-scale diffuse reflection system achieves a soft halo without glare, and the light transmittance of Example 1 is 1.2g / cm 3The density is about 20% lower than that of traditional methods, and the transportation and installation costs are significantly reduced. The UV aging color difference ΔE=0.8, and the color remains almost unchanged after 5 years of outdoor use, breaking the limitation of traditional materials that turn yellow in 1-2 years. Bio-based resin replaces petroleum-based materials, and VOC emissions are reduced by 60%. At the same time, dual curing compresses the cycle to 3 hours, taking into account both green manufacturing and industrial mass production capabilities.

[0083] Those skilled in the art will appreciate that the modules and algorithm steps of the various examples described in conjunction with the embodiments disclosed herein can be implemented with electronic hardware, or a combination of computer software and electronic hardware. Whether these functions are performed in hardware or software depends on the specific application and design constraints of the technical solution. Professional and technical personnel can use different methods to implement the described functions for each specific application, but such implementation should not be considered to be beyond the scope of this application.

[0084] In addition, each functional module in each embodiment of the present application may be integrated into one processing module, or each module may exist physically separately, or two or more modules may be integrated into one module.

[0085] The above is only a specific implementation method of the present application, but the scope of protection of the present application is not limited to this. Any technician familiar with this technical field can easily think of changes or replacements within the technical scope disclosed in this application, which should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.

[0086] Finally: The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection of the present invention.

Claims

1. A method for producing an artificial light-transmitting stone relief, characterized in that: The following steps are involved: S1: Bio-based polyurethane resin and aliphatic isocyanate were mixed in a ratio of 4:1, followed by addition of polyacrylate and silicone in a low-speed mixer at 200 rpm for 3 minutes; S2: The mixture in S1 was added with nano-silica and glass beads in batches, and the mixture was dispersed in a disperser at 500 rpm for 5 minutes until no lumps were formed. The mixture was then vacuum degassed for 5 minutes, and finally 0.1% of a transparent organic pigment azo dye was added and stirred to prepare a slurry. S3: Pour 0.5mm thick slurry on the bottom of the mold, then let it stand for 5 minutes and irradiate it with UV lamp for 10 minutes to cure it. Place the slurry in the relief area of ​​the mold upside down, use 0.3-0.5MPa air pressure imprinting technology to embed the slurry into the mold texture and let it stand for 15 minutes until it is semi-cured. Finally, pour 1mm thick slurry on the relief to wrap the relief structure, and then vacuum degas. S4: Place the whole in a UV curing box and irradiate for 20 minutes to cure the surface layer, then transfer to a 60°C oven for 1 hour, then cool to room temperature and remove the mold; S5: Polish the relief with 800# and 2000# sandpaper respectively.

2. The method for making an artificial light-transmitting stone relief according to claim 1, wherein: The use of bio-based polyurethane and nano-silica as described in S1 instead of traditional epoxy resin meets environmental protection requirements.

3. The method for making an artificial light-transmitting stone relief according to claim 1, wherein: The nano-silica and glass beads described in S1 form a diffuse reflection system, which produces a soft halo effect when light passes through, avoiding the glare of traditional processes.

4. The method for making an artificial light-transmitting stone relief according to claim 1, wherein: The raw materials used in S1 replace natural stone, which reduces the cost by 30-50%, and can be customized into different shapes and patterns according to needs.

5. The method for making an artificial light-transmitting stone relief according to claim 1, wherein: The 0.1% azo dye used in S2 can achieve a bright and light-transmitting color, making the light transmittance ≥70%.

6. The method for making an artificial light-transmitting stone relief according to claim 1, wherein: The process described in S3 uses layered casting and UV-heat dual curing, which shortens the relief curing cycle by 50%.

7. The method for making an artificial light-transmitting stone relief according to claim 1, wherein: The vacuum degassing in S3 can make the overall density of the relief uniform.

8. The method for making an artificial light-transmitting stone relief according to claim 1, wherein: The relief in S4 has a Shore hardness of 60-70A and a bending strength of ≥30MPa, which is superior to traditional resin relief and can withstand daily collisions.

9. The method for making an artificial light-transmitting stone relief according to claim 1, wherein: The aliphatic isocyanate used in the relief of S4 has yellowing resistance and will not change color after 5 years of outdoor use, which is better than aromatic polyurethane.

10. The method for making an artificial light-transmitting stone relief according to claim 1, wherein: The density of the relief in S4 is 1.2-1.5g / cm 3 It is only half the size of natural stone, making it easy to install, transport, and create large-scale wall reliefs.